2021
DOI: 10.1002/ajoc.202100616
|View full text |Cite
|
Sign up to set email alerts
|

Dehalogenation and Desulfonation from Aryl and Alkyl Compounds with a Cobalt Catalyst in the Presence of Alcohol

Abstract: Easy dehalogenation of bromo-, chloro-aryl and alkyl derivatives is performed in the presence of a cobalt catalyst, manganese as reductant, and alcohol as hydrogen donor. This method tolerates a variety of functional groups with different electronic properties. Noteworthy examples of desulfonation are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…On the other hand, alcohol is regarded as an ideal alternative hydrogen source due to its benign nature and easy operation. Only a few examples have been reported in transition metal‐catalyzed transfer hydro‐dehalogenation of halides with alcohols [6b,7c,8b,c,10b,12] . Among the alcohols, ethanol, as one of the most important alcohols, is abundant, sustainable, and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, alcohol is regarded as an ideal alternative hydrogen source due to its benign nature and easy operation. Only a few examples have been reported in transition metal‐catalyzed transfer hydro‐dehalogenation of halides with alcohols [6b,7c,8b,c,10b,12] . Among the alcohols, ethanol, as one of the most important alcohols, is abundant, sustainable, and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Halogenated organic compounds are a common class of environmental pollutants, and the reduction of C–halogen (C-X) bonds to C–H bonds is not only an important tool for detoxifying them but also a fundamental organic transformation in organic synthesis. Although the ideal dehalogenation effect can be achieved by using highly reducible hydrated electronic or noble metal cocatalyst such as Pd or Rh, the cost is high. , Using solar energy as the driving force to reduce the C–X bond into a C–H bond can not only avoid the generation of harmful by-products but also alleviate the energy crisis. At present, different types of photocatalysts have been used for the reduction of C-X bonds. For example, Zhao et al reported a composite material with Cu particles loaded on TiO 2 surface to co-catalyze polybrominated pollutants .…”
Section: Introductionmentioning
confidence: 99%